2014
DOI: 10.1007/s10461-014-0726-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-Specific Condom Attitudes Predict Condom Use Among STD Clinic Patients with both Primary and Non-primary Partners

Abstract: Although condom use differs by partner type (i.e., primary vs. non-primary partner), attitudes towards condom use are typically measured without consideration of partner type. This study investigated the predictive utility of condom attitudes measured separately by partner type. Participants were 270 patients (37% women, 72% Black) recruited from a publicly-funded STD clinic who reported having both primary and non-primary partners. They completed a computerized survey assessing relationship-specific condom at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…As female actor number of lifetime sex partners increased, intentions to use condoms decreased. Considered alongside the finding that increased number of partners also related to intentions to remain monogamous, this might indicate unwillingness to use condoms in a committed relationship (Macaluso et al, 2000; Senn et al, 2014). This is concerning, given that females with more lifetime sex partners also tended to be with males reporting more partners, which could put them at higher risk for HIV and other STIs, as well as repeat pregnancy (Meade & Ickovics, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As female actor number of lifetime sex partners increased, intentions to use condoms decreased. Considered alongside the finding that increased number of partners also related to intentions to remain monogamous, this might indicate unwillingness to use condoms in a committed relationship (Macaluso et al, 2000; Senn et al, 2014). This is concerning, given that females with more lifetime sex partners also tended to be with males reporting more partners, which could put them at higher risk for HIV and other STIs, as well as repeat pregnancy (Meade & Ickovics, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For perception of partner behavior, control variables included relationship length and partner age. For condom use and monogamy intentions, control variables included relationship length and actor age, given that age may reflect more opportunity to engage in unsafe behaviors, and relationship length could impact knowledge of partner behaviors and commitment to the relationship, a known predictor of condom use (Macaluso et al, 2000; Senn, et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…A person, whose cognitive self-evaluation or judgement of their capabilities is high, will tend to use a condom with greater confidence. Empirical evidence has demonstrated that people with high levels of condom use self-efficacy make successful decisions regarding sexual health, both ability to use condoms as ability to reject sexual risk behaviors [22,23,[26][27][28][29]67]. Self-efficacy is not a static characteristic, it can be altered by internal personal factors in the form of cognitive and affective events.…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that the behavior was related to behavioral intention (.45); behavioral intention was related to attitudes (.58) and the subjective norm (.39); attitudes were associated with behavioral beliefs (.56); norms were associated with normative beliefs (.46); and perception of control was associated with the behavioral intention (.45) and condom use (.25). In the implementation model it has been observed that the intention to use condoms predicts significantly its use during sex; the perception of control and attitudes are the best predictors preventive behavior; the subjective norm has more influence on the formation of intent to action on specific groups, such as adolescents [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[23] The association of sexual satisfaction and condom use may reflect influence of higher levels of coital frequency in dyads with high levels of sexual satisfaction, with consequent rapid decline in condom use. [24] Alternatively, common perceptions that condoms interfere with pleasure and sexual function may lead dyads to abandon condoms in order to preserve high levels of sexual satisfaction. [25, 26]…”
Section: Discussionmentioning
confidence: 99%